Effect of chronic restraint stress on body weight of male Sprague Dawley rats - Sadia Moazzam; Irfan Afzal Mughal; Noor Ul Ain Irfan; Ilqa Attique; Fareeha Zaheer; Asma Irfan (Journal of Rawalpindi Medical College, 2023)
Background: